Feeding habits of the frog Pleurodema diplolistris (Anura, Leptodactylidae) in Quaternary sand dunes of the Middle Rio São Francisco, Bahia, Brazil - Santos, José Wellington Alves dos; Damasceno, Roberta Pacheco; Rocha, Pedro Luís Bernardo da (Phyllomedusa: Journal of Herpetology, 2003)
In this work, we investigate the feeding habits of Pleurodema diplolistris, the most abundant anuran species of the São Francisco sand dunes, during a period of slightly over one year. The fieldwork was undertaken during four excursions to a sand dune in the semiarid Caatinga, Brazil, and the analyses were based on stomach contents. Pleurodema diplolistris were not active during the dry season. The important food categories in diet were Isoptera (winged forms), Coleoptera, and Formicidae. Small and large animals had different food consumption patterns: small frogs showed positive electivity for termites and large frogs, for ants. This pattern was strongly influenced by large male food electivity. High levels of termites consumption occurred during the days of greater capture success. The pattern of high consumption of termites detected here is different from that described in another study on lizards from the same locality and sampled in the same periods. We discuss alternative hypotheses that could explain the observed patterns.